Kelp patch size and density influence secondary productivity and diversity of epifauna. Issue 3 (19th December 2019) - Shelamoff, Victor; Layton, Cayne; Tatsumi, Masayuki; Cameron, Matthew J.; Edgar, Graham J.; Wright, Jeffrey T.; Johnson, Craig R.
Abstract : Habitat‐forming ecosystem engineers are the foundation of many marine ecosystems where they support diverse and productive food‐webs. A reduction in their patch size or density may affect the productivity, biodiversity and stability of these ecosystems. We determined the effects of different densities and patch sizes of Ecklonia radiata (the dominant kelp in southern Australia) on the secondary productivity, species richness, diversity and community structure of understory epifaunal invertebrates and how associated environmental covariates modified by kelp affected those patterns. We assessed sub‐canopy epifauna across 28 artificial reefs with transplanted E. radiata consisting of seven different patch sizes (0.12–7.68 m 2 ) crossed with four kelp densities (0–16 kelp m −2 ) over two years. Epifaunal secondary productivity associated with both natural algal and standardised rope fibre habitats decreased with patch size and was elevated when kelp was absent, however, it was also high in natural habitat when there was a high density of kelp. Epifaunal productivity was positively associated with sub‐canopy light and water flow but negatively associated with the biomass of the dominant understory alga, Ulva sp. Epifaunal diversity declined with a reduction in reef size as did richness which correlated with a loss of algal species richness. Community structure of epifauna also differed between small and large reefs, between reefs with and without kelp, between rope habitats at the centre and at the edge of reefs, and within natural habitat between reefs supporting high and low densities of kelp. Overall, these results indicate complex effects of E. radiata decline on epifaunal communities, with high secondary productivity associated with dense kelp stands, but also areas without kelp that are dominated by turf algae. While the loss of standing kelp from rocky reefs may result in declines in epifaunal biodiversity, where turf algae replaces kelp, the reefs may still support high secondary productivity.